AI in the B2B sales process of international SMEs - Kailio, Sami (My University, 2024)
Artificial intelligence (AI) has become easily available for micro, small, and medium-sized enterprises (SMEs) in recent years. This study investigates the adoption and utilisation of AI in Finnish international SMEs from a business-to-business (B2B) sales perspective. AI´s current benefits and challenges and what types of tools are used are studied through qualitative interviews with sales leaders from six companies. The companies operate in digital industries, either developing software or offering consulting in digital services. Findings show that companies primarily use AI to enhance the existing abilities of salespeople and increase efficiency by automating repetitive tasks. In an international context, AI was often used similarly as in domestic settings. Additionally, in internationalsales, AI was used for market analysis, localisation, and customer engagement. However, challenges such as limited resources, integration into existing systems, and resistance to change slow down widescale adoption in the companies. Despite these obstacles, interviewees express optimism about AI's future role in B2B sales. The research complements the existing literature by providing information on practical experiences and perspectives on AI deployment. The managerial implications highlight the importance of strategic thinking in the adoption of AI, differentiation from competitors and continuous learning to achieve long-term benefits. For example, companies should prepare for the impact of wider adoption of AI and consider which stages of the sales process AI will have the greatest impact on. In addition, due to their availability, easily accessible AI tools cannot create a unique competitive advantage. Companies must strategically assess, for example, the differentiation of sales material produced by generative AI in a market where competitors can produce similar content. The process of AI adoption is largely comparable to the introduction of other new technologies. Efficient implementation emphasises the time available for learning new things, perceived ease of use and communicating the benefits to the end user. Special attention was paid to the integration of AI tools into existing systems, which was felt to significantly increase utilisation.

Tekoälyn käyttö on tullut pk-yrityksille helpommin saataville viime vuosina. Tämä tutkimus tarkastelee tekoälyn käyttöönottoa ja hyödyntämistä kansainvälisesti toimivissa suomalaisissa pkyrityksissä B2B-myynnin näkökulmasta. Tekoälyn nykyisiä hyötyjä ja haasteita sekä sitä, millaisia työkaluja käytetään, selvitetään kuuden yrityksen myyntijohtajien laadullisilla haastatteluilla. Haastatellut yritykset toimivat digitaalisilla toimialoilla joko kehittäen ohjelmistoja tai tarjoten asiantuntijapalveluita digitaaliseen liiketoimintaan liittyen. Tulokset osoittavat, että yritykset käyttävät tekoälyä ensisijaisesti myyjien olemassa olevien kykyjen parantamiseen ja tehokkuuden lisäämiseen automatisoimalla toistuvia tehtäviä. Kansainvälisessä kontekstissa tekoälyä käytettiin usein samalla tavalla kuin kotimaisissa ympäristöissä. Lisäksi kansainvälisessä myynnissä tekoälyä hyödynnettiin markkina-analyysiin, lokalisointiin ja kommunikointiin. Haasteet, kuten rajalliset resurssit, integraatiot olemassa oleviin järjestelmiin ja muutosvastarinta, hidastavat kuitenkin laajamittaista käyttöönottoa yrityksissä. Näistä esteistä huolimatta haastateltavat suhtautuvat optimistisesti tekoälyn tulevaan rooliin B2B-myynnissä. Tutkimus täydentää olemassa olevaa kirjallisuutta tarjoamalla tietoa käytännön kokemuksista ja näkökulmia tekoälyn käyttöönottoon. Tutkimuksen käytännön merkitys ja päätöksentekoehdotukset korostavat strategisen ajattelun merkitystä tekoälyn käyttöönotossa, erottautumista kilpailijoista ja jatkuvaa oppimista pitkän aikavälin hyötyjen saavuttamiseksi. Yritysten tulisi esimerkiksi valmistautua tekoälyn laajemman käyttöönoton vaikutuksiin ja pohtia mihin myynnin prosessin vaiheisiin tekoälyllä on suurimmat tehostavat merkitykset. Lisäksi helposti saatavilla olevat tekoälytyökalut eivät voi saatavuutensa takia luoda uniikkia kilpailuetua itsessään vaan yritysten tulee strategisesti arvioida esimerkiksi generatiivisen tekoälyn tuottaman myyntimateriaalin erottautuvuutta markkinassa, jossa kilpailijoiden on mahdollista tuottaa vastaavaa sisältöä. Suurilta osin tekoälyn käyttöönoton prosessi on verrattavissa muiden uusien teknologioiden käyttöönottoon. Tehokkaassa käyttöönotossa korostuu käytettävissä oleva aika uuden opetteluun, koettu käytön helppous ja hyötyjen kommunikointi loppukäyttäjälle. Erityistä huomiota annettiin tekoäly työkalujen integroitavuudelle olemassa oleviin järjestelmiin, jonka koettiin merkittävästi lisäävän käyttöä.
Keywords: internationalisation; business-to-business commerce; artificial intelligence; digitalisation; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business